2006
DOI: 10.4141/p06-106
|View full text |Cite
|
Sign up to set email alerts
|

Common bunt resistance gene Bt10 located on wheat chromosome 6D

Abstract: . 2006. Common bunt resistance gene Bt10 located on wheat chromosome 6D. Can. J. Plant Sci. 86: 1409-1412. Knowledge of the chromosomal location of disease resistance genes assists in their identification and classification. The determination of the chromosomal location in wheat of the common bunt (Tilletia tritici and T. laevis) resistance gene Bt10 was the goal of this study. Doubled haploid lines were developed from a cross between bunt susceptible Glenlea and bunt resistant AC Taber carrying Bt10. The doub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
40
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 9 publications
1
40
0
Order By: Relevance
“…The two studies also used different inoculum sources: the Blizzard study used the common bunt races T-19 or T-19 and L-16, while this study used the composite dwarf bunt races. Additional common bunt HPR QTL have been reported from other resistance sources, including: 7A (Fofana et al 2008; Dumalasová et al 2012), 7B (Dumalasová et al 2012; Knox et al 2013), 5B (Dumalasová et al 2012; Singh et al 2016), 4D (Singh et al 2016), and 6D (Menzies, et al 2006; Singh et al 2016), while none of these HPR QTL were detected in the present study. Singh et al (2016) found that the common bunt HPR QTL co-localized with other beneficial traits including height and rust resistance.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The two studies also used different inoculum sources: the Blizzard study used the common bunt races T-19 or T-19 and L-16, while this study used the composite dwarf bunt races. Additional common bunt HPR QTL have been reported from other resistance sources, including: 7A (Fofana et al 2008; Dumalasová et al 2012), 7B (Dumalasová et al 2012; Knox et al 2013), 5B (Dumalasová et al 2012; Singh et al 2016), 4D (Singh et al 2016), and 6D (Menzies, et al 2006; Singh et al 2016), while none of these HPR QTL were detected in the present study. Singh et al (2016) found that the common bunt HPR QTL co-localized with other beneficial traits including height and rust resistance.…”
Section: Discussionmentioning
confidence: 92%
“…However, that haplotype is also present in a number of additional lines with known putative resistance genes and also present in the differential lines for Bt5 , Bt8 , Bt9 , Bt10 , Bt12 , and Bt13 (Table 5). It is possible that the QTL contains one or more of these known HPR genes other than Bt10 , as Bt10 is already mapped to chromosome 6D (Menzies et al 2006). The IDO444 haplotype is present in Promontory, while absent in Manning, Deloris, and Utah-100, and these cultivars all have the same putative HPR gene combination including Bt - 3 , Bt - 9 , and Bt - 10 (Table 5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bt7 (Sel. 50077) has been located on chromosome 2D by Metzger (after McIntosh et al 1998), and Bt10 (PI 178383 9 Elgin) on chromosome 6D (Menzies et al 2006). Recently two papers appeared that attributed common bunt resistance to chromosome 1B (Fofana et al 2008;Wang et al 2009).…”
Section: Introductionmentioning
confidence: 95%
“…Tilletia caries) and Tilletia laevis (syn. Both the incidence and severity of common bunt have been controlled in the Canadian prairies, largely by introgressing resistance genes such as Bt10 and Bt8 (Menzies et al, 2006;McCallum and DePauw, 2008;Hiebert et al, 2011). It reduces both grain yield and quality through the formation of bunt balls that replace the grain with brown black that results in unpleasant-smelling spores (Martens et al, 1984).…”
mentioning
confidence: 99%